World religions and Islam : a critical study - Rafiabadi, Hamid Naseem (New Delhi : Sarup & Sons, 2003)
"To define religion is one of the very difficult tasks as every interpreter attempts to give it a subjective twist to suit his individual or community aspirations. However, there has been various definitions provided by scholars to this intricate enterprise. The idea of God formed in one generation by one set of human beings could be meaningless in another. Indeed, the statement "I believe in God" has no objective meaning, as such, but like any other statement only means something in context, when proclaimed by a particular community. Consequently there is no one unchanging idea contained in the word "God": instead, the word contains a whole spectrum of meanings, some of which are contradictory or mutually exclusive. Had the notion of God not had this flexibility, it would not have survived to become one of the great human ideas. When one conception of God has ceased to have meaning of relevance, it has been quietly disregarded and replaced by a new theology. Yet if we look at three religions, i.e., Judaism, Christianity and Islam, it becomes clear that there is no objective view of "God": each generation has to create the image of God that works for it. In this book I have attempted to present world religions in a very broader context vis-a-vis Islam. In the introduction Islamic response to world religions has been shown in a comparative perspective. There is an article on the secular challenges that have rendered religious phenomenon vulnerable to all sorts of attacks. Thus the book is a collection of valuable articles written by eminent scholars belonging to various religious denominations , and researchers and teachers of Islamic studies. This book is also meant to cater to the requirements of students of comparative religions and theology"--Dust jacket.
Includes bibliographical references and indices.
Keywords: Islam -- Relations -- Christianity; Islam -- Relations -- Judaism